Transcriptional activation by the acidic domain of Vmw65 requires the integrity of the domain and involves additional determinants distinct from those necessary for TFIIB binding. - Walker, S (1993)
In this work we have examined the requirements for activity of the acidic domain of Vmw65 (VP16) by deletion and site-directed mutagenesis of the region in the context of GAL4 fusion proteins. The results indicate that the present interpretation of what actually constitutes the activation domain is not correct. We demonstrate, using a promoter with one target site which is efficiently activated by the wild-type (wt) fusion protein, that amino acids distal to residue 453 are critical for activity. Truncation of the domain or substitution of residues in the distal region almost completely abrogate activity. However, inactivating mutations within the distal region are complemented by using a promoter containing multiple target sites. Moreover, duplication of the proximal region, but not the distal region, restores the ability to activate a promoter with a single target site. These results indicate some distinct qualitative difference between the proximal and distal regions. We have also examined the binding of nuclear proteins to the wt domain and to a variant with the distal region inactivated by mutation. The lack of activity of this variant is not explained by a lack of binding of TFIIB, a protein previously reported to be the likely target of the acidic domain. Therefore some additional function is involved in transcriptional activation by the acid domain, and determinants distinct from those involved in TFIIB binding are required for this function. Analysis of the total protein profiles binding to the wt and mutant domains has demonstrated the selective binding to the wt domain of a 135-kDa polypeptide, which is therefore a candidate component involved in this additional function. This is the first report to provide evidence for the proposal of a multiplicity of interactions within the acidic domain, by uncoupling requirements for one function from those for another.